Peningkatan Kualitas Produksi UKM Percetakan di Karangpilang Surabaya dan Krian Sidoarjo - Kristanto, Titus; Muliawati, Eka Cahya; Arief, Rachman; Hidayat, Syaiful (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2018)
Mitra 1 (Purnama Advertising) is a printing business engaged in printing and graphic design, owned by Mr. Purnomo. Business location Purnama Advertising is very strategic close to the highway, due to many people skipped. Mitra 2 (Smart Jaya) owned by Mr. Hidayat handles a very simple print design. Smart Jaya business location is very strategic close to the school. The problems faced by Partners 1 and Partner 2 are constrained in the field of online marketing, due to the limited cost of the Partners. The purpose of the devotion activity is to develop an independent printing business and have a broad insight on print design and graphic design. The solutions offered from the devotion activities are providing printing machines and hot press machines, mentoring media marketing, production management and marketing training. The outcomes of the IbM program are scientific publications in ISSN Journals, national seminar publications, and online promotional media.